Stress Testing the Global Economy to Climate Change-Related Shocks in Large and Interconnected Economies - Tovar Mora, Camilo (IMF Working Papers; Working Paper ;, 2022)
We stress test the global economy to extreme climate change-related shocks on large and interconnected economies. Our analysis (i) identifies large and interconnected economies vulnerable to climate change-related shocks; (ii) estimates these economies' external financing needs-at-risk due to these shocks, and (iii) quantifies the spillovers to the global economy using a global network model. We show that large and interconnected economies vulnerable to climate change could trigger a drain of USD 1.8 trillion in international reserves (2 percent of 2019's global GDP). Domestic and multilateral macroeconomic policies can help reduce these global lossess to about USD 0.8 trillion. The scenario highlights the importance of considering global spillovers when assessing the impact of climate change-related shocks.